Tafsir Al-Qur’an Hibarna: Telaah Ideologi dan Hermeneutika - Siti Mariatul Kiptiyah; Aftonur Rosyad; Moh Safrudin; Kholid Junaidi (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This article examines a model of Qur’anic interpretation in Indonesia through a study of Tafsir Hibarna written by Iskandar Idries in 1933. The study aims to analyze the characteristics of Idries’ interpretive approach and the intellectual background that shaped his exegetical thought. This research employs a qualitative method with a hermeneutical approach to the text. The findings reveal that Idries developed a distinctive model of Qur’anic exegesis within the Indonesian context, particularly in terms of its writing style and its incorporation of local linguistic and cultural elements. Furthermore, Tafsir Hibarna reflects a tendency toward puritan Islamic ideology, as indicated by its critique of practices such as taqlid, superstition (tahayul), innovation (bid‘ah), myth (khurafat), and polytheism (shirk). This tendency is closely related to Idries’ background as a da‘wah activist in an early 20th-century modernist Islamic organization in Indonesia. These findings suggest that local Qur’anic exegesis not only represents religious understanding but is also shaped by the social and ideological context of the interpreter.